2014
DOI: 10.1111/bju.12905
|View full text |Cite
|
Sign up to set email alerts
|

Association of androgen‐deprivation therapy with excess cardiac‐specific mortality in men with prostate cancer

Abstract: ObjectivesTo determine if androgen-deprivation therapy (ADT) is associated with excess cardiac-specific mortality (CSM) in men with prostate cancer and no cardiovascular comorbidity, coronary artery disease risk factors, or congestive heart failure (CHF) or past myocardial infarction (MI). Patients and MethodsIn all, 5077 men (median age 69.5 years) with cT1c-T3N0M0 prostate cancer were treated with brachytherapy with or without neoadjuvant ADT (median duration 4 months) between 1997 and 2006. Fine and Gray co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 25 publications
(24 reference statements)
1
38
0
1
Order By: Relevance
“…Authors also found that the risk for developing a CV disease was the highest during the fi rst 6 months of the treatment in men who experienced two or more cardiovascular events before they started the therapy with agonists of GnRH. This supports the opinion that those patients threated with ADT and an preexisting CV disease may be at the greatest risk (2)(3)(4)(5)33). Increased cardiovascular toxicity in patients undergoing a short-term ADT was confi rmed by another authors (38).…”
Section: Clinical Studiessupporting
confidence: 57%
See 1 more Smart Citation
“…Authors also found that the risk for developing a CV disease was the highest during the fi rst 6 months of the treatment in men who experienced two or more cardiovascular events before they started the therapy with agonists of GnRH. This supports the opinion that those patients threated with ADT and an preexisting CV disease may be at the greatest risk (2)(3)(4)(5)33). Increased cardiovascular toxicity in patients undergoing a short-term ADT was confi rmed by another authors (38).…”
Section: Clinical Studiessupporting
confidence: 57%
“…Unfortunately, ADT has also an adverse effects on cardiovscular system. According to several authors an increased attention should be given to patients with a history of cardiovascular problems (2)(3)(4)(5). The study by Keating et al (6) is one of the landmark studies investigating ADT associated cardiovascular risk.…”
Section: Introductionmentioning
confidence: 99%
“…Aktuelle Studien und Übersichtsar-beiten legen nahe, dass unter ADT bei Patienten mit fPCa und einer KV-Vorgeschichte ein erhöhtes Risiko für erneute KV-Ereignisse besteht [6,20,30]. Dieses Risiko scheint zwischen den GnRHAgonisten Leuprorelin und Goserelin und -Antagonisten unterschiedlich ausgeprägt, wobei der etwas teurere GnRHAntagonist ein vorteilhafteres Risikoprofil aufweist [2].…”
Section: Hintergrundunclassified
“…8,9,16 These tests for interaction did not reach significance for either patient age (P = .82) or history of pre-RT CE (P = .40).…”
Section: Resultsmentioning
confidence: 82%
“…In an analysis of randomized trial data, D'Amico et al reported increased risk of cardiac death after ADT among patients with moderate to severe comorbidity. 8 Publications from Nanda et al and Ziehr et al demonstrated that, in a cohort of 5077 men with clinically localized prostate cancer, ADT use increased all-cause mortality 9 and cardiac-specific mortality 16 only among patients with a prior history of congestive heart failure or acute MI. The authors of these studies reasonably conclude that, in patients with an already compromised cardiovascular status, ADT may precipitate cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 99%